Upaya Peningkatan Minat Belajar Siswa Melalui Aplikasi Google Meet Dengan Menggunakan Model Pembelajaran Direct Learning Pada Pelajaran Al Quran Hadits Kelas 8 Di Mts Al-Ma`ruf Tahun Ajaran 2020/2021 - Harahap, Rizky Syahpril; Arifin, Haris Nursyah; Dinansyah, Dinansyah (Faidatuna, 2021)
Learning is the process of learning for students using educational principles and learning theory which are the main determinants of success. In the research that will be carried out, the author wishes to make an effort in order to increase the interest in learning of 8th graders, especially in the subject of Al Quran Hadith through the Google Meet application with a direct learning model. In this case, the writer wants to focus research on two points including how to increase the interest in learning of 8th grade students in the subject of Al Quran Hadith through the Google Meet application and using the direct learning method and what are the supporting and inhibiting factors in providing improvement efforts to 8th grade students in Al Quran Hadith subjects through the Google Meet application and using the direct learning method. The objectives to be achieved by the author in this study are to determine the causes of decreased interest in learning for 8th grade students using online learning in the subject of Al Quran Hadith at MTs Al-Ma'ruf and for supporting and inhibiting factors in providing improvement efforts to 8th grade students. in the Al Quran Hadith subject through the Google Meet application and using the direct learning method. This type of research is descriptive with a qualitative approach, namely the method of presentation, interpretation of data on the factors in the field. To obtain valid and accurate data, the authors used three data collection techniques, namely interviews, observation and documentation. The results of the research from the thesis made by the author are that there is an increase in the interest in learning of 8th grade students in Al Quran Hadith subjects through the Google Meet application with the Direct learning model, although in it there are several obstacles related to efforts to increase interest in learning carried out by teaching teachers.